Ductile inclusions in rail, subject to compressive rolling–sliding contact - Garnham, J.E.; Ding, R.-G.; Davis, C.L. (Wear, 2010)
▶ Ductile inclusions become ‘pizza’ shaped planes of weakness near-surface in rails. ▶ Ductile inclusions facilitate flake crack initiation and growth in dry contact. ▶ Ductile inclusions can initiate RCF cracking in water lubricated contact. ▶ Ductile inclusion number density and size vary significantly depending on rail steel source. Driven by a requirement for increased performance and cost-effectiveness, the basic pearlitic microstructures of rail steels are being progressively refined and novel microstructures are being developed. With such progress, increased attention must be paid to potential ‘weak spots’ in the microstructure such as non-metallic inclusions. For the past few decades, rail steels have become progressively cleaner with regard to harmful brittle inclusions, however the effect of rolling–sliding contact forces on nominally benign, ductile inclusions requires further consideration. This work examines the characteristics of ductile, Mn-based inclusions in used rail and rail test discs. Where the structure near-surface has been subject to a high component of transverse creepage, ductile, axially aligned inclusion ‘stringers’ become strain-flattened to form planes of weakness along which micro-cracks initiate and propagate, thus facilitating wear and rolling contact fatigue (RCF) cracking. The progression of shape change of these ductile inclusions approaching the contact surface has been examined by optical and electron microscopy including focussed ion beam (FIB) analysis. As-manufactured ductile inclusions shapes and distributions have also been surveyed with respect to the (geographical) source of the rail steel. Comparative data for these different steel sources are given.